Sources of subcortical projections to the superior colliculus in the ferret. - Jiang, Z; Moore, DR; King, A (1997)
We have identified brainstem and other subcortical afferents to the superior colliculus (SC) in the ferret, by examining the pattern of retrograde labelling that resulted from unilateral injections of red and green fluorescent latex microspheres or of wheat germ agglutinin conjugated to horseradish peroxidase into different regions of this midbrain nucleus. Labelled neurons were found in many structures, including somatosensory, visual and auditory nuclei. These subcortical inputs are almost all bilateral, although most are primarily ipsilateral. Despite some differences in organization, the subcortical projections to the ferret SC broadly resemble those described in other species. Following injections of red and green microspheres in either the rostral and caudal or the medial and lateral regions of the SC, double-labelled cells usually accounted for less than 10% of the total number of retrogradely labelled cells, indicating that most of the subcortical neurons project to discrete regions of the SC. Many of these afferents show some topographic organization, which is much more evident along the rostrocaudal axis of the SC than in the medial-lateral dimension. The intercollicular projection is restricted mainly to the rostral SC and demonstrates a point-to-point organization. Most of the subcortical structures caudal to the central region of the SC were labelled mainly by the tracers injected in caudal SC, while those rostral to this region, including the zona incerta and the pretectal nuclei, were labelled largely by injections in rostral SC. These findings suggest that projections originating from nuclei posterior to the central region of the SC terminate principally in caudal SC whereas afferents from structures anterior to the central region project largely to rostral SC.